1987
DOI: 10.1002/j.1460-2075.1987.tb02352.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of alfalfa mosaic virus coat protein gene confers cross-protection in transgenic tobacco and tomato plants

Abstract: A chimeric gene encoding the alfalfa mosaic virus (AlMV) coat protein was constructed and introduced into tobacco and tomato plants using Ti plasmid-derived plant transformation vectors. The progeny of the self-fertilized transgenic plants were significantly delayed in symptom development and in some cases completely escaped infection after inoculated with AIMV. The inoculated leaves of the transgenic plants had significantly reduced numbers of lesions and accumulated substantially lower amounts of coat protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…Transgenic plants expressing coat protein genes of virus pathogens show delayed disease development or are resistant to infection upon inoculation with the respective virus. This form of resistance has been shown for tobacco mosaic virus, alfalfa mosaic virus, tobacco rattle virus, cucumber mosaic virus, potato virus X and potyviruses (Powell Abel et al, 1986;Loesch-Fries et al, 1987;VanDun et al, 1987;VanDun & Bol, 1988;Tumer et al, 1987;Cuozzo et al, 1988 ;Hemenway et al, 1988;Hoekema et al, 1989;Stark & Beachy, 1989). The wide applicability of this method offers promise for coat protein-mediated protection of citrus plants.…”
Section: -9945 © 1991 Sgmmentioning
confidence: 94%
“…Transgenic plants expressing coat protein genes of virus pathogens show delayed disease development or are resistant to infection upon inoculation with the respective virus. This form of resistance has been shown for tobacco mosaic virus, alfalfa mosaic virus, tobacco rattle virus, cucumber mosaic virus, potato virus X and potyviruses (Powell Abel et al, 1986;Loesch-Fries et al, 1987;VanDun et al, 1987;VanDun & Bol, 1988;Tumer et al, 1987;Cuozzo et al, 1988 ;Hemenway et al, 1988;Hoekema et al, 1989;Stark & Beachy, 1989). The wide applicability of this method offers promise for coat protein-mediated protection of citrus plants.…”
Section: -9945 © 1991 Sgmmentioning
confidence: 94%
“…This form of coat proteinmediated protection has now been demonstrated for a number of different viruses including alfalfa mosaic virus (A1MV; Van Dun et al, 1987;Tumer et al, 1987;Loesch-Fries et al, 1987), cucumber mosaic virus (CMV; Cuozzo et al, 1988), tobacco rattle virus , tobacco streak virus and PVX (Hemenway et al, 1988;Hoekema et al, 1989). More recently, simultaneous resistance to two viruses, PVX and potato virus Y, has been reported in transgenic potato plants expressing the nucleocapsid proteins from each of these viruses (Lawson et al, 1990).…”
Section: Potato Virus S (Pvs) Is a Member Of The Carlavirus Groupmentioning
confidence: 99%
“…serology, peptide mapping, amino acid composition). Furthermore, the coat protein region is of interest because recent reports have shown that transgenic plants which express a viral coat protein (including CMV coat protein) are protected against infection by the corresponding intact virion (Powell-Abel et al, 1986;Tumer et al, 1987;Loesch-Fries et al, 1987;Nelson et al, 1987Nelson et al, , 1988Van Dun et al, 1987;Cuozzo et al, 1988;Hemenway et al, 1988).…”
Section: Introductionmentioning
confidence: 99%